Data Structures and Algorithm Analysis In C++ [3rd ed.] - Weiss, Mark Allen (India: Pearson, 2014)
This book features a full C++ language update and incorporation of the Standard Template Library. There is new treatment of lists, stacks, queues and trees and an entire chapter dedicated to amortized analysis and advanced data structures such as the Fibonacci heap.
Keywords: Programming -- C++; Algorithm Design; Advanced Data Structures